Taxes and Charities: An International Comparison - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 1996)
The research questions posed in this study are: * What organizations qualify for charitable status under Canadian tax law and regulations? * Is the Canadian definition of charitable status too broad? Too narrow? * Can other countries provide models for Canada with regard to definitions of charitable status? * What kind of tax measures are used by other countries to support charities? Have these measures resulted in demonstrably greater levels of charitable donations or a more robust charitable sector? To answer these questions, this study had the following objectives: * to determine how other countries have adjusted their definition of charitable status to achieve fairness and accommodate changing public perceptions of the nature of a charity; * to highlight the best mechanisms being used by other countries to ensure that qualified charitable organizations have access to the tax system for fundraising and other purposes; * to evaluate the comparative costs and benefits of alternative approaches to restructuring the tax system. The countries included in this survey are the United States, the United Kingdom, France, Australia, New Zealand, Mexico and Japan.
Keywords: Taxes; Charities